2020
DOI: 10.3390/ijms21124543
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bisphenol a on the Nitrergic Nervous Structures in the Domestic Porcine Uterus

Abstract: Bisphenol A (BPA) is one of the most common environmental pollutants among endocrine disruptors. Due to its similarity to estrogen, BPA may affect estrogen receptors and show adverse effects on many internal organs. The reproductive system is particularly vulnerable to the impact of BPA, but knowledge about BPA-induced changes in the innervation of the uterus is relatively scarce. Therefore, this study aimed to investigate the influence of various doses of BPA on nitrergic nerves supplying the uterus with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Moreover, resiniferatoxin and tetrodotoxin induced a drop in cholinergic, nNOS-immunoreactive urinary-bladder-supplying neuronal cells in PCG with an additional increase in non-cholinergic, nNOS-positive perikarya, similar to the current findings [24]. Studies on ER-impacting Bisphenol A confirmed a measurable impact on the number of uterine nerve fibers, in which it significantly increased the population of nitrergic nerves in either low or high doses [41].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, resiniferatoxin and tetrodotoxin induced a drop in cholinergic, nNOS-immunoreactive urinary-bladder-supplying neuronal cells in PCG with an additional increase in non-cholinergic, nNOS-positive perikarya, similar to the current findings [24]. Studies on ER-impacting Bisphenol A confirmed a measurable impact on the number of uterine nerve fibers, in which it significantly increased the population of nitrergic nerves in either low or high doses [41].…”
Section: Discussionsupporting
confidence: 85%
“…In the reproductive system BPA causes changes in the uterus manifested by the increase in the thickness of the endometrium and number of fibroblasts, as well as by the inhibition of apoptosis [ 43 , 44 ]. These changes are accompanied by disturbances in estrus cycle, embryo implantation after fertilization, motor activity of the uterus, sex hormones levels and secretion of active substances by nervous structures supplying the uterine [ 45 , 46 , 47 , 48 ]. Exposure to BPA may contribute to development of endometriosis and cervical cancer [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…The neuronal structures in the muscular layer of the aortic arch were studied using double immunofluorescence labeling. Labeling was performed according to the method described previously by Rytel et al [5]. The method comprised the following stages (performed in rt): (1) drying of the slices (1 h); (2) treatment with solution consisting of 10% normal goat serum, 0.1% bovine serum albumin, 0.01% NaN3, 0.25% Triton x-100, and 0.05% thimerosal in phosphate-buffered saline (PBS) for 1 h; (3) treatment with a combination of two primary antibodies from various species (Table 1): the first was directed against a pan-neuronal marker (protein gene product 9.5 (PGP 9.5)) and the second against one of the other neuronal factors studies, i.e., CART, CGRP, nNOS, PACAP, VIP, GAL, or SOM (overnight); (4) incubation with the combination of secondary antibodies labeled with appropriate fluorochromes (Table 1) to visualize the complex "antigen-primary antibody" (1 h); ( 5) covering with buffered glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its common use, BPA is present in the following components: tap water, soil, air, and dust [4]. It may penetrate into human and animal organisms through the digestive tract/system, respiratory system, skin, and placenta (in utero) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%